PERAN PENYULUH PERTANIAN DDALAM ADOPSI BIOSAKA PADA KELOMPOK TANI DI KAPANEWON KARANGMOJO KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Luthfi Wisnu Gifta Febrian; Wahyu Setya Ratri; Nanang Kusuma Mawardi (JURNAL ILMIAH AGRITAS, 2025)
This study aims to examine the role of agricultural extension workers in the adoption of Biosaka innovation among farmer groups in Kapanewon Karangmojo, Gunungkidul Regency. A descriptive, quantitative approach was used, with data collected through observation and documentation, and questionnaires distributed to 30 respondents selected via snowball sampling. The results indicate that the six indicators of extension roles (motivator, educator, catalyst, communicator, consultant, and facilitator) generally received positive responses from farmers. The consultant role scored highest, while the facilitator role scored the lowest. The level of Biosaka adoption was also considered high, particularly at the awareness stage, but decreased at the actual adoption stage. Simple linear regression analysis showed a significant influence of extension workers' roles on Biosaka adoption, here are improvements in extension workers' roles are followed by increased adoption of Biosaka. These findings highlight the importance of optimizing extension roles to support the successful adoption of environmentally friendly agricultural innovations.